Peningkatan Kreativitas Anak Melalui Program Pelatihan Keychain Berbasis Daur Ulang Di Yayasan Mizan Amanah Krukut - Afipah Apriliana; Alfiola Deswinta Zahra; Dianti Juliana Salsabilah (Journal of Conflict and Social Class (JCSC), 2024)
This activity aims to develop children's creativity through a training program that teaches them to make keychains using recycled materials at Yayasan Mizan Amanah Krukut. The program is designed as an educational and participatory activity, using old materials to stimulate imagination, fine motor skills, and environmental awareness in children. The method used is action research with both qualitative and quantitative approaches, through observation, practical assistance, and evaluation of the participants' work. The training is carried out step by step, starting with introducing the materials, designing the artwork, and then the actual making of the keychains. The results of this activity show an increase in children's creativity, shown through their courage in expressing ideas, variety in their artwork designs, and improved confidence. The program also raises children's awareness about creative use of waste. Therefore, the training in making keychains based on recycling has proven to be an effective creative learning medium that is both educational and sustainable.